Isolation of Plasma Proteins from Bovine Blood by Cold Ethanol Precipitation and Anion Exchange Chromatography - Ekwumemgbo, Patricia Adamma; Kagbu, James Adagadzu; Nok, Andrew Jonathan; Omoniyi, Israel Kehinde; Ameh, Paul Ocheme; Oladunni, Nathaniel (Journal of Nepal Chemical Society, 2010)
Plasma (100.00 ml) obtained from bovine blood by centrifugation was fractionated into seven precipitates by cold ethanol precipitation. The yield (amount) of proteins in the precipitates calculated from the standard curve of BSA was 1160.83 mg, 806.57 mg, 1149.94 mg, 8.79 mg, 19.88 mg, 21.98 mg, and 13.97 mg respectively, while the total amount of protein obtained was 3180.00 mg. The precipitates were fractionated into 25 fractions each by Anion Exchange Chromatography (AEC) and the amount of protein in each fraction was obtained by Bradford protein assay. SDS-PAGE analysis was performed on the fractions with proteins and their estimated molecular weights were obtained with the aid of the molecular weight marker. The result indicated that cold ethanol precipitation and anion exchange chromatographic techniques are valuable tools for the purification of bovine blood to obtain high grade α, β and γ-fibrinogen, IgM (μ-globulin), IgG (γ -globulin), alpha (α –globulin), β-globulin (E-globulin) and albumin. Keywords: Plasma; Chromatography; Electrophoresis; Albumin; Fibrinogen; Globulin DOI: 10.3126/jncs.v26i0.3624 Journal of Nepal Chemical Society Vol. 26, 2010 Page: 2-12